2006
DOI: 10.1016/j.ejcts.2006.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Does bilateral ITA grafting increase perioperative complications?☆Outcome of 4462 patients with bilateral versus 4204 patients with single ITA bypass

Abstract: CABG using both ITAs can be performed routinely with good clinical results and low mortality. Compared with single ITA grafting, sternal and bleeding complications were slightly increased. Diabetes mellitus, BITA grafting, duration of surgery but not obesity or COPD could be identified as independent risk factors for sternal complications. Dialysis-dependent renal failure, EF<30%, emergent cases, and the absence of BITA grafting were predictors for increased perioperative mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 29 publications
2
43
2
2
Order By: Relevance
“…The long-term benefit of BIMA use is relatively low in the elderly. BIMA use may increase the risk of sternal wound infection, 23,24 especially in patients with diabetes mellitus. 25 However, other studies have shown that the skeletonization technique reduces the risk of wound infection after BIMA use in diabetic patients 26 and that BIMA grafts provide some benefits even in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term benefit of BIMA use is relatively low in the elderly. BIMA use may increase the risk of sternal wound infection, 23,24 especially in patients with diabetes mellitus. 25 However, other studies have shown that the skeletonization technique reduces the risk of wound infection after BIMA use in diabetic patients 26 and that BIMA grafts provide some benefits even in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…After 10 years of experience with BIMA CABG, Gansera et al noted increased OR and aortic cross clamp times among BIMA patients compared with single IMA CABG patients. In addition, patients receiving BIMA grafting had higher rates of bleeding requiring postoperative mediastinal reexploration (2.9% vs. 0.6%) along with increased rates of wound complications [95]. However, they also noted that nearly one full additional distal graft was completed when both IMAs were used and, most importantly, BIMA grafting was associated with improved 30-day survival, particularly among diabetic patients, compared with only one IMA graft.…”
Section: Bilateral Internal Mammary Artery Conduitsmentioning
confidence: 97%
“…However, they also noted that nearly one full additional distal graft was completed when both IMAs were used and, most importantly, BIMA grafting was associated with improved 30-day survival, particularly among diabetic patients, compared with only one IMA graft. [95]. In this same study, a grafting strategy not incorporating 2 IMA conduits was an independent predictor of perioperative mortality, directly disputing biases that BIMA grafting is associated with increased perioperative complications [95].…”
Section: Bilateral Internal Mammary Artery Conduitsmentioning
confidence: 99%
See 2 more Smart Citations